Alice's adventures in wonderland eaudiobook - Carroll, Lewis (Ascent Audio, 2010)
This tale, beloved by children and adults everywhere, follows Alice as she falls down a rabbit hole into a fantasy world, where she meets The Mad Hatter, the Ugly Duchess, the Mock Turtle, the Queen of Hearts and the Cheshire Cat—each character more eccentric than the last. Lewis Carroll, the master of sublime nonsense, has created one of the most famous and fantastic novels of all time. He plays with logic in ways that have given the story lasting popularity and not only stirred our imagination but revolutionized literature.